CD34 positive cells as endothelial progenitor cells in biology and medicine - Hassanpour, Mehdi; Salybekov, Amankeldi A.; Kobayashi, Shuzo; Asahara, Takayuki (Frontiers in Cell and Developmental Biology, 2023)
CD34 is a cell surface antigen expressed in numerous stem/progenitor cells including hematopoietic stem cells (HSCs) and endothelial progenitor cells (EPCs), which are known to be rich sources of EPCs. Therefore, regenerative therapy using CD34+ cells has attracted interest for application in patients with various vascular, ischemic, and inflammatory diseases. CD34+ cells have recently been reported to improve therapeutic angiogenesis in a variety of diseases. Mechanistically, CD34+ cells are involved in both direct incorporation into the expanding vasculature and paracrine activity through angiogenesis, anti-inflammatory, immunomodulatory, and anti-apoptosis/fibrosis roles, which support the developing microvasculature. Preclinical, pilot and clinical trials have well documented a track record of safety, practicality, and validity of CD34+ cell therapy in various diseases. However, the clinical application of CD34+ cell therapy has triggered scientific debates and controversies in last decade. This review covers all preexisting scientific literature and prepares an overview of the comprehensive biology of CD34+ cells as well as the preclinical/clinical details of CD34+ cell therapy for regenerative medicine.